Studying the wind-induced vibrations of a traffic signal structure through long term health monitoring. (15th November 2021) - Tsai, Li-Wei; Alipour, Alice
Highlights: A cantilevered traffic signal structure with vertical traffic lights was monitored for a year. Acceleration data at the mast arm tip was used to study wind-induced behavior. Strain data at the pole-to-arm connection was used to evaluate fatigue damage. The orientation of traffic lights on a mast arm was noticed to affect wind-induced behavior. Attached vertical traffic lights can reduce the likelihood of vortex-induced vibration. Abstract: Recent failures of traffic signal structures have showcased the vulnerability of such structures to wind loading. During the wind-induced vibration of the mast arm, the large mass of the mast arm creates high-level stress at the pole-to-arm connection. Additionally the low mechanical damping results in accumulationof stress cycles ewhich could cause fatigue damage at the pole-to-arm connection. In this study, a traffic signal structure with three vertical traffic lights was selected for long-term health monitoring. The monitored acceleration data at the mast arm tip was used to study the wind-induced behavior and was compared with the theoretical analysis results. The monitored strain data at the pole-to-arm connection was used to evaluate the fatigue damage. Low stress ranges were recorded most of the time, which indicates that the wind-induced fatigue damage might not be a significant concern for the monitored traffic signal structure. However, high stress ranges have been recorded at high wind speeds, indicating fatigue damage can still be an issue at higher wind speed regions. The performance of monitored traffic signal structure was compared with those in the literature. An apparent discrepancy was noticed between their wind-induced behaviors, and the orientation of the attached traffic lights was identified as a key parameter to influence the wind-induced behavior. It was found that at low wind speed, attached vertical traffic lights can reduce the likelihood of vortex-induced vibration and, as a result, lower the stress range at the pole-to-arm connection.